2011
DOI: 10.1159/000331012
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Child Awareness and Expectations of Child Overweight

Abstract: Objective: We investigated mothers’ and children’s assessments of body weight and their expectations about perceived body size in relation to overweight of the children. Methods: We performed a case-control study of 111 cases of overweight children and 149 controls of non-overweight children (mean age 8.1 years) and their mothers. All were examined and interviewed about their assessment of body weight and their perception of a normal, attractive and acceptable body size. Results: Case children were less able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…This finding is in line with those reported in a recent study of seventeen obese 8-12-year-olds in the US Midwest in which 42 % of these overweight children reported that they were underweight or normal weight (22) . Similar trends have been reported internationally, as demonstrated by a study in China showing that underestimation of childhood overweight is common among both children and mothers in China, particularly for children with the highest BMI (19) , and a European study (23) showing that overweight children were less able than normal weight children to correctly assess their own body weight. In the present study 42?9 % of the children had an accurate estimation that approximately one-third of US children are overweight.…”
Section: Discussionsupporting
confidence: 79%
“…This finding is in line with those reported in a recent study of seventeen obese 8-12-year-olds in the US Midwest in which 42 % of these overweight children reported that they were underweight or normal weight (22) . Similar trends have been reported internationally, as demonstrated by a study in China showing that underestimation of childhood overweight is common among both children and mothers in China, particularly for children with the highest BMI (19) , and a European study (23) showing that overweight children were less able than normal weight children to correctly assess their own body weight. In the present study 42?9 % of the children had an accurate estimation that approximately one-third of US children are overweight.…”
Section: Discussionsupporting
confidence: 79%
“…Material and methods have previously been described [16] and are dealt with only briefly here. The study was based on the Danish National Birth Cohort (DNBC) [17], a longitudinal large-scale study involving data collection when the children were 7 years old, with a follow-up of the mothers' and the children's current situation, and based on whether the children had or had not become overweight, regardless of the mothers weight.…”
Section: Methodsmentioning
confidence: 99%
“…When recruiting for the present case-control study in autumn 2007, 11,249 children had turned 7, and data from their follow-up questionnaires were registered. After meeting the inclusion and exclusion criteria (described in [16]), 2,846 pairs were potentially eligible, from which 471 pairs were randomly selected within candidate case and control groups. Of these, 241 pairs were invited to participate as cases and 230 as controls [16].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations